The sea of the dead - Wolverton, Barry (Wolverton, Barry <<The>> chronicles of the black tulip, 2017)
"After the harrowing and life-changing events at the Dragon's Gate, Bren wants nothing more than to make his way back to England. Finding the answers to the great mysteries he'd been chasing only found him questioning why he'd ever pursued them in the first place, and now he's lost his best friend, forever. There's nothing left for him but to return home and hope his father hasn't given up on him. But just because Bren is done with adventure does not mean adventure is done with him. On his way to escape from China, Bren is gifted a rare artifact, with a connection to a place no one has set foot upon. Soon he's fallen in with a mysterious Indian noblewoman bent on discovering an ancient power and leading her country against colonial rule. The only way home, it seems, is through helping her--and as Bren wonders what she's willing to sacrifice in order to return home a hero, he must ask himself the same question"--Jacket flap